Transfer pricing auditing and tax forestalling by Multinational Corporations: a game theoretic approach - Mashiri, Eukeria; Dzomira, Shewangu; Canicio, Dzingirai; McMillan, David (Cogent OA, 2022)
The problem of revenue leakages through transfer pricing remains unabated, and an examination of possible causes is a continuum. This study provides a nuanced examination of the interaction between MNCs and the tax consultants (TCs) which is treated with mixed views in the existing literature. The role of TCs in aiding and abetting taxpayers into abusive transfer pricing (TP) has implications for policy especially in situations where the tax administration systems are porous. Based on a theoretical review (deductive theorising) the study moves from exploring broad and general aspects of the game theory to applying them to tax forestalling through TP by Multinational Corporations (MNCs). The study critiques the assumptions of game theory and explores the influence of TCs in TP decision making processes by MNCs. It gives a theoretical explanation (interpretive phenomenology) on game theory attempting to promote a deeper understanding of TP by MNCs. The study contributes to knowledge by exploring a confluence of three TP-related aspects which have been treated in isolation in existing literature. The findings show that the tacit collusion between TCs and MNCs sanitise the abusive TP activities by minimising the chances of the MNCs shenanigans being recognised by the tax authority due to information asymmetry. Further, the mediating role of TCs is polarised and benefits the TCs and the MNCs who will share the spoils at the expense of the tax authority.